Observations of ion upflow and 630.0 nm emission during pulsating aurora - Godbole, Niharika H.; Lessard, Marc R.; Kenward, David R.; Fritz, Bruce A.; Varney, Roger. H.; Michell, Robert G.; Hampton, Don (Frontiers in Physics, 2022)
In this study, we report observations made by filtered (557.7 and 630.0 nm) All-Sky Imagers located at Poker Flat, Alaska alongside Poker Flat Incoherent Scatter Radar data for an event observed on 5 February 2017. Together, the data indicate ion upflow in the vicinity of pulsating aurora. Additionally, the data show a strong 630.0 nm (red-line) auroral emission. Observations of pulsating aurora are typically reported at 557.7 and 427.8 nm, as these wavelengths are more sensitive to high-energy (∼ tens of keV) electron precipitation. In contrast, 630.0 nm emission is generated preferentially by low-energy soft electron precipitation (∼ hundreds of eV), and is less commonly observed. The All-Sky Imager data discussed here are unusual in that they suggest regions of enhanced soft electron precipitation in conjunction with enhanced ambipolar electric fields, which are a known factor contributing to ion outflow.